A 14‐3‐3 Mode‐1 Binding Motif Initiates Gap Junction Internalization During Acute Cardiac Ischemia. (9th April 2014) - Smyth, James W.; Zhang, Shan‐Shan; Sanchez, Jose M.; Lamouille, Samy; Vogan, Jacob M.; Hesketh, Geoffrey G.; Hong, TingTing; Tomaselli, Gordon F.; Shaw, Robin M.
<x xml:space="preserve">Abstract</x> Altered phosphorylation and trafficking of connexin 43 (Cx43) during acute ischemia contributes to arrhythmogenic gap junction remodeling, yet the critical sequence and accessory proteins necessary for Cx43 internalization remain unresolved. 14‐3‐3 proteins can regulate protein trafficking, and a 14‐3‐3 mode‐1 binding motif is activated upon phosphorylation of Ser373 of the Cx43 C‐terminus. We hypothesized that Cx43Ser373 phosphorylation is important to pathological gap junction remodeling. Immunofluorescence in human heart reveals the enrichment of 14‐3‐3 proteins at intercalated discs, suggesting interaction with gap junctions. Knockdown of 14‐3‐3τ in cell lines increases gap junction plaque size at cell–cell borders. Cx43S373A mutation prevents Cx43/14‐3‐3 complexing and stabilizes Cx43 at the cell surface, indicating avoidance of degradation. Using Langendorff‐perfused mouse hearts, we detect phosphorylation of newly internalized Cx43 at Ser373 and Ser368 within 30 min of no‐flow ischemia. Phosphorylation of Cx43 at Ser368 by protein kinase C and Ser255 by mitogen‐activated protein kinase has previously been implicated in Cx43 internalization. The Cx43S373A mutant is resistant to phosphorylation at both these residues and does not undergo ubiquitination, revealing Ser373 phosphorylation as an upstream gatekeeper of a posttranslational modification cascade necessary for Cx43 internalization. Cx43Ser373 phosphorylation is a potent target for therapeutic interventions to preserve gap junction coupling in the stressed myocardium. <inline-graphic xlink:href="ark:/27927/pgh4dcq6" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />